Effect of Liquid Injection Arrangements on Injection Flow Rate of a Laboratory-Scale Venturi Scrubber - Zheng, Guangzong; Chen, Bo; Li, Jishen; Shi, Kaiyi; Gu, Haifeng (Frontiers in Energy Research, 2019)
As the core device of a filtered containment venting system (FCVS), Venturi Scrubber is an efficient device to scrub the radioactive gases and aerosols before release into the atmosphere. The design concept of Multi-Venturi Scrubber System makes the laboratory-scale venturi scrubber research more valuable. This paper studied the injection flow rate of Venturi Scrubber in different injection arrangements. The liquid is injected horizontally and vertically to the throat at different radial position of (i) at the wall of throat, (ii) at the half radius of throat, and (iii) at the center of Venturi Scrubber throat with a nozzle of diameter 4 mm. Throat gas velocities range from 0 to 190 m/s. A constant level water tank was installed to keep water level constant during the injection process. The results showed that liquid injection modes significantly affect the injection performance. The arrangements of straight tube at center and elbow tube at center had larger injection flow rate among the others, and the injection flow rate increased as the throat gas velocity increased. The conventional wall opening (i.e., straight tube at the wall) injection method had the worst injection performance. This study provides a valuable reference for the liquid injection arrangement and structural design of the Venturi Scrubber.